2011
DOI: 10.1002/cncy.20153
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of metabolic phenotypes in malignant pleural effusions

Abstract: BACKGROUND: The sensitivity of conventional cytology for the detection of malignant cells in pleural effusion is insufficient. GLUT1 and CAIX are the hallmarks of metabolic change in cancer cells. The aim of this study was to evaluate the usefulness of GLUT1 and CAIX expression to the detection of cancer cells in pleural effusions. METHODS: A total of 150 pleural effusions were subjected to immunocytochemical staining for GLUT1 and CAIX expression. According to their cytological diagnosis and etiology, these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…46 Importantly, CAIX activity is required for primary metastatic breast cancer cell growth under hypoxic conditions that favor the expansion of CSCs and previously noted to be highly appropriate for assessing the sensitivity of CSCs to therapeutic agents. 21 These findings further confirm the relevance of CAIX-specific pharmacologic inhibitors as future treatment for metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Importantly, CAIX activity is required for primary metastatic breast cancer cell growth under hypoxic conditions that favor the expansion of CSCs and previously noted to be highly appropriate for assessing the sensitivity of CSCs to therapeutic agents. 21 These findings further confirm the relevance of CAIX-specific pharmacologic inhibitors as future treatment for metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In each sample, metastatic tumor cells displayed highly specific staining for CAIX, which was notably absent from other cell populations, similar to previous reports. 46 Subsequently, we cultured three PE samples to assess the functional requirement for CAIX activity. Viable PE samples from three different patients were collected and cultured under hypoxic TS-forming conditions confirmed as highly appropriate for assessing the sensitivity of CSCs to therapeutic agents.…”
Section: Cd44mentioning
confidence: 99%
“…10 In this regard, CAIX is commonly used as an ancillary immunostain to aid in the diagnosis of metastatic renal cell carcinoma. 4 Recent studies 6,11 showed that higher CAIX levels by immunocytochemical studies and/or by enzyme-linked immunosorbent assays are seen in malignant effusions in contrast to benign effusions. These studies suggest that benign-appearing, CAIX-immunoreactive, "mesotheliallike" cells seen on a Papanicolaou stain are likely to represent atypical/malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 A recent article noted that immunostaining for CAIX on pleural effusion samples can serve as a complementary tool in distinguishing carcinoma from reactive mesothelial cells. 6 In addition, two studies noted CAIX expression in malignant pleural mesotheliomas and in metastatic renal cell carcinoma to the lung. 2,7 Furthermore, Ramsey et al 7 also observed CAIX immunostaining in one case of mesothelial hyperplasia of the pleura.…”
Section: Conclusion: Caix Can Be a Useful Ancillary Marker For Identmentioning
confidence: 99%
“…However, the sensitivity of these noninvasive techniques is only 40-70% [3]. The sensitivity of conventional cytology for the detection of malignant cells in pleural effusion is insufficient [4].…”
Section: Introductionmentioning
confidence: 99%